2009
DOI: 10.1007/s00127-009-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish version of the Family Assessment Device

Abstract: Proposals to improve and adapt questionnaire are discussed with a view to make it applicable to cultures other than the one it was developed. Theoretical models relating to psychosocial aspects such as family functioning, albeit compatible in some areas, should be viewed with caution in cultures different to that in which the model originates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 87 publications
11
50
0
1
Order By: Relevance
“…The Brazilian version showed a high internal consistency (Cronbach's alpha = 0.910), which is similar to those found in other versions 1,8,22,23 . With regard to the internal consistency of the FAD dimensions, the Brazilian version showed similar scores to those found in studies using comparable samples.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The Brazilian version showed a high internal consistency (Cronbach's alpha = 0.910), which is similar to those found in other versions 1,8,22,23 . With regard to the internal consistency of the FAD dimensions, the Brazilian version showed similar scores to those found in studies using comparable samples.…”
Section: Discussionsupporting
confidence: 79%
“…Family functioning studies have raised great interest in the literature given that they identify the dynamics and influence of psychosocial variables on the detection of both general diseases and psychiatric disorders 1 . Family comprises a complex system to be assessed because each has a peculiar way of life, deeply influenced by cultural factors 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our exploratory factor analysis are consistent with the literature since no research found a good fit between the McMaster Model and the data collected in cross-cultural studies [3,4,5,7]. Results on the clinimetric version of the FAD are also consistent with those proposed for the clinimetric version of the neuroticism subscale of the Neuroticism, Extraversion, Openness Personality Inventory (NEO-PI) [10].…”
Section: Tablesupporting
confidence: 79%
“…It has 6 subscales and a General Functioning scale, which assesses the overall health/pathology of the family. The FAD has shown an adequate internal consistency [3,4,5] and moderated correlations with other self-report family assessment questionnaires [6]. Its discriminant validity, between families of medical patients and families of controls, has been studied with heterogeneous results [6], while the discriminant validity among families of different groups of psychiatric patients and normal samples is good [6].…”
Section: Tablementioning
confidence: 99%